PHYSICAL ACTIVITY AS A NON-PHARMACOLOGICAL ADJUNCT THERAPY IN THE MANAGEMENT OF RELAPSING-REMITTING MULTIPLE SCLEROSIS: A NARRATIVE REVIEW OF CURRENT EVIDENCE - Juszkiewicz, Dawid; Kiełczewski, Krzysztof; Zaręba, Agnieszka; Dłużewska, Magdalena; Fetner, Barbara; Stankowska, Patrycja; Gebert, Zuzanna; Ilkiv, Ivanna; Kucharska, Agata; Adler, Konrad (International Journal of Innovative Technologies in Social Science, 2026)
Background: Historically, patients with Relapsing-Remitting Multiple Sclerosis (RRMS) were advised to avoid physical exertion to prevent symptom exacerbation. However, recent evidence has catalyzed a paradigm shift, positioning physical activity as a critical disease-modifying intervention. Objective: This narrative review aims to summarize the current state of knowledge regarding the role of physical activity as a non-pharmacological adjunct therapy in RRMS, focusing on its biological mechanisms, symptomatic impact, and clinical safety. Methods: An analysis of contemporary literature was conducted, focusing on the molecular, structural, and psychosocial effects of exercise in individuals with RRMS. Results: Physical activity modulates the central nervous system by upregulating neurotrophic factors, such as Brain-Derived Neurotrophic Factor (BDNF), which support synaptic plasticity and axonal survival. It induces a favorable systemic cytokine shift, reducing pro-inflammatory markers (TNF-α, IL-17). Clinically, structured exercise—comprising aerobic training, progressive resistance training, and mind-body interventions—effectively mitigates pathological fatigue, improves mobility, and supports cognitive processing speed. High-intensity protocols and task-oriented circuit training have shown potential neuroprotective effects, including the preservation of gray matter volume. Modern management of thermal sensitivity (Uhthoff’s phenomenon) and personalized intensity based on the Expanded Disability Status Scale (EDSS) ensure a high safety profile. Conclusion: Physical activity acts in synergy with Disease-Modifying Therapies (DMTs), creating a "dual-track" strategy that addresses both inflammatory activity and neurodegenerative decline. Initiating exercise within the "Window of Opportunity" early after diagnosis is essential to maximize the preservation of neurological reserve. Physical activity should be considered a fundamental pillar of multidisciplinary MS care, vital for functional independence and improved quality of life.